Mechanisation of agricultural work in sub-Saharan Africa: study report - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Mechanisation of agricultural work in sub-Saharan Africa: study report